Mild Pelvicalyceal System Dilatation Observed by Ultrasound as a Sign of Acute Appendicitis - Al-Najjar, Dr. Suhel M. (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background and Objectives: The positive pelvicalyceal changes observed by ultrasound in suspected acute appendicitis cases confuse the mind in taking a decision for surgical interferences or medical management. This study aims to analyze the effect of pelvicalyceal system dilatation on the diagnosis of acute appendicitis and the associated factors of mild pelvicalyceal system dilatation in acute appendicitis. Methods: The study assessed 326 suspected acute appendicitis in addition to 260 cases of functional dyspepsia as a control group. Ultrasound of the abdomen was a principal imaging study in the research with the emphasis on pelvicalyceal dilatation, combined in some cases with KUB, CT and Doppler-Ultrasonography. Results: Out of 326 cases of acute appendicitis, ultrasound revealed that 34% had RPCSD and 7% had bilateral BPCSD. The pelvicalyceal dilatations were observed in 54.5% of the acute recurrent cases or chronic appendicitis and suppurative appendicitis were 30%. The recorded length of appendix ranged from 3.8 to 18 cm. The position of appendix were mainly pelvic (59%) followed by retrocecal (36.4%). Conclusions : The Pelvicalyceal system dilatation observed by ultrasound in the suspicious acute appendicitis patients can be served as a sign for diagnosis of acute appendicitis in states of hesitation.